Modern Condition of Locations of Municipal Solid Waste in a Residential Buffer Suburb of the City of Almaty - KALIASKAROVA, Z. K.; IKANOVА, A. S.; ALIYEVA, Zh. N.; BEKKULIEV, A. A. (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).08, 2018)
The modern development of human economic activity, the increase in the number of people result in environmental pollution by wastes of their production and consumption. The purpose of this work is to analyze the status the existing waste disposal sites in the city of Almaty. The benchmark data for the analysis and monitoring were the satellite images of the solid waste sites from the Sasplanet database and the Google Earthmap client program. The materials were decoded using the ArcGIS 10.3 multifunctional software. According to the results of decoding of space images and monitoring of the dynamics of boundary changes, we investigated 2 operating landfills, 1 closed landfill and 5 identified unauthorized landfills. The maps of the current status of solid waste landfills were compiled. The analysis of long-term changes in the boundaries of existing municipal solid wastes disposal sites for the period of 2003-2016 was carried out. On the basis of visual observation and decoding of space images, maps of the current state of solid waste landfills, as well as data on the compliance of landfills with the main sanitary norms of the Republic of Kazakhstan. The use of methods of decoding allows the most effective cope with the tasks of environmental monitoring aimed at identifying waste disposal sites, assessing their status and dynamics of development in space and time.